2022
DOI: 10.31219/osf.io/8et9g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-news websites expose people to more political content than news websites: Evidence from browsing data in three countries

Abstract: Most scholars focus on the prevalence and democratic effects of (partisan) news exposure. This focus misses large parts of online activities of a majority of politically disinterested citizens. Although political content also appears outside of news outlets and may profoundly shape public opinion, its prevalence and effects are under-studied at scale. This project combines three-wave panel survey data from three countries (total N = 6,892) with online behavioral data from the same participants (119.7M visits).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…With regard to the newsfeed stimulus, we focused on securing internal validity by keeping (1) the amount of post elements that would typically be found in a Facebook post in the newsfeed consistent, that is, there was no post without a title or picture, and (2) the distribution of political posts consistent, which may have affected external validity (cf. Vraga et al, 2015; Wojcieszak et al, 2024). Nonetheless, our results provide general tendencies to which newsfeed post elements users pay attention to in different conditions and can lay the groundwork for more detailed research on the attention to one manipulated newsfeed post element on specific devices and in different usage environments.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the newsfeed stimulus, we focused on securing internal validity by keeping (1) the amount of post elements that would typically be found in a Facebook post in the newsfeed consistent, that is, there was no post without a title or picture, and (2) the distribution of political posts consistent, which may have affected external validity (cf. Vraga et al, 2015; Wojcieszak et al, 2024). Nonetheless, our results provide general tendencies to which newsfeed post elements users pay attention to in different conditions and can lay the groundwork for more detailed research on the attention to one manipulated newsfeed post element on specific devices and in different usage environments.…”
Section: Discussionmentioning
confidence: 99%
“…Most research in political communication focuses on the impact of news exposure or political social media use on attitudes, beliefs, and behaviors. However, as use of news media and dependence on professional journalism declines and use of social media increases (Auxier & Anderson, 2021; Wojcieszak et al, 2023), it becomes vital to consider how the social media information environment as a whole may affect politically relevant attitudes and policy preferences. Our results showed that aspirational use of social media was positively associated with anti-intellectualism but had no association with distrust of science.…”
Section: Discussionmentioning
confidence: 99%
“…We see these results as evidence for the need for further research on how patterns of social media use and entertainment content on social media may be associated with political attitudes and social norms (Delli Carpini, 2019; Gerbner & Gross, 1976; Matthes et al, 2023). This work is increasingly important as people now tend to receive more political messages from non-political sources than from political sources online (Wojcieszak et al, 2023). As fewer people regularly consume news media, lifestyle influencers creating aspirational content have the potential to reach a broad range of individuals, particularly younger and less politically engaged audiences who are often overwhelmed by news media and rely on trusted influencers for political information (Cotter & Thorson, 2022; Harff, 2022; Schmuck et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median number of video visits per person was 76 (SD 1,165). The details on the large-scale project, including extensive informed consent and IRB approvals are reported in (16,50). the increase in percentage of news recommendations is higher 188 ‡ In short, our measure of news recommendations and exposures encompasses all news videos, consistent with past work (36,44), and our measure of political videos encompasses all videos that were not part of news channels.…”
mentioning
confidence: 87%